Pendampingan Identifikasi Bahan Bacaan Ramah Anak Berbasis Budaya Lokal Etnis Ngadhu Bhaga di Sekolah Dasar Kecamatan Bajawa - Wau, Maria Patrisia; Meka, Marsianus; Kedhi, Maria Anjelina (Civiliza Publishing, 2025)
This community service program (PKM) is an integral part of the Thematic Community Service Program (KKN) carried out by lecturers and students of the Seventh Semester of the Elementary School Teacher Education Study Program (PGSD) at STKIP Citra Bakti. This PkM focused on the importance of providing and utilizing reading materials in elementary schools that not only meet child-friendly criteria (appropriate for age, language, and developmental psychology) but are also based on specific local culture. Specifically, this activity is directed at identifying reading materials that integrate the values and heritage of the Ngadhu Bhaga Ethnic Group, which is the dominant cultural identity in the Bajawa District area. This activity was carried out in seven elementary schools in the Bajawa District, Ngada Regency. The approach used was a qualitative approach with a descriptive survey type. Data collection techniques were carried out through 3 techniques, namely collection inventory, semi-structured interviews, and document analysis. Based on the identification results, it can be concluded that the availability of reading materials in elementary schools in Bajawa District, Ngada Regency, is still not optimal in supporting the strengthening of local culture-based literacy. Child-friendly reading materials that explicitly highlight Bajawa local values, stories, and wisdom were found to be very minimal, which resulted in hampering efforts to contextualize learning and strengthen students' cultural identity.